2011
DOI: 10.1071/fp11137
|View full text |Cite
|
Sign up to set email alerts
|

Salinity drives host reaction in Phaseolus vulgaris (common bean) to Macrophomina phaseolina

Abstract: Abstract. Productivity of Phaseolus vulgaris L. (common bean) is often limited by diseases such as seedling blight and root and stem rot caused by the fungus Macrophomina phaseolina and by abiotic stresses such as salinity. This paper reports controlled environment studies examining the interaction of biotic (M. phaseolina) and abiotic (NaCl) stresses. Studies were conducted at 32 C. On potato dextrose agar, the growth of two isolates of M. phaseolina (M1, M2) was differentially stimulated by 40 mM NaCl with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Increased soil salt concentration results in enhanced susceptibility to soil borne diseases in tomato (Triky-Dotan et al 2005) and other crop species (Al-Sadi et al 2010;You et al 2011), and similar trends are observed under water deficit (Jordan et al 1984). Observations of the effects of abiotic stress on foliar pathogens are on the other hand mixed, with studies reporting either enhanced (Achuo et al 2006;Wiese et al 2004), or decreased resistance (Roubtsova and Bostock 2009;Sanogo 2004).…”
Section: Introductionmentioning
confidence: 50%
“…Increased soil salt concentration results in enhanced susceptibility to soil borne diseases in tomato (Triky-Dotan et al 2005) and other crop species (Al-Sadi et al 2010;You et al 2011), and similar trends are observed under water deficit (Jordan et al 1984). Observations of the effects of abiotic stress on foliar pathogens are on the other hand mixed, with studies reporting either enhanced (Achuo et al 2006;Wiese et al 2004), or decreased resistance (Roubtsova and Bostock 2009;Sanogo 2004).…”
Section: Introductionmentioning
confidence: 50%
“…It would be oversimplification if we were to assume root rot to be only a host × pathogen interaction. Studies in various crops have clearly demonstrated that the disease outcome is greatly influenced by genotype (host/pathogen) × environment interactions [ 80 , 83 , 88 , 97 , 98 ]. Previous results have indicated that soil water deficit has a major role in predisposing mulberry to charcoal rot [ 11 ], and soil moisture levels below 30% increase disease severity [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, high concentrations of BCH increased the fungus growth rate and stimulated its development in vitro. Increased salinity in the PDA culture medium, resulting from the addition of NaCl + CaSO4 or CaSO4, stimulated the development and infection of two M. phaseolina isolates [18]. Biochars produced at 500 ºC presented higher values of electrical conductivity (EC) than those produced at lower temperatures [19].…”
Section: Resultsmentioning
confidence: 99%